Relação entre a formação da liderança e os fatores socioambientais de risco à saúde no trabalho - Rodrigues Alevato, Hilda Maria (Boletim Técnico do Senac, 2003)
This text intends to contribute for potencializing the discussion about mental and psychological health at work. It aims to call attention for a type of risk, named Loco Neurotic Syndrom, or SLN, which is hardly feeded on the inattentive attitude in the face of its first symptons. It also wants to emphasize the central role of leading and authority models in the developing of psychological suffering.